1969
DOI: 10.1037/h0082504
|View full text |Cite
|
Sign up to set email alerts
|

The effects of step size, response mode and knowledge of results upon achievement in programmed instruction.

Abstract: This study explored the likelihood that current inconsistencies in findings relating to the programming variables of step size (SS), response mode (RM) and knowledge of results (KR) might stem from the tendency of past research to investigate these variables in isolation from each other. Such an approach fails to make provision for the observation of possible interactions. Accordingly, four levels of KR (O, 50% variable-ratio, 100%, 100% plus incentive), three levels of RM (overt, covert, covert plus random ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…of those, five showed KCR to be more effective than no feedback (anderson et al, 1971, Exp. i & ii;Clariana, Ross, & morrison, 1991;Grant, mcavoy, & Keenan, 1982;Roper, 1977), five found no significant difference (anderson et al, 1972;Gaynor, 1981;Gilman, 1969;morrison, Ross, Gopalakrishnan, & Casey, 1995;Pysh, Blank, & lambert, 1969), and one found no feedback to be superior to KCR (Pridemore & Klein, 1995). The other, moore and smith (1964), found that KCR via teaching machine produced better within-program performance than KR and no feedback with construction-response materials, but not with multiple-choice materials.…”
Section: Knowledge Of Correct Responsementioning
confidence: 99%
See 1 more Smart Citation
“…of those, five showed KCR to be more effective than no feedback (anderson et al, 1971, Exp. i & ii;Clariana, Ross, & morrison, 1991;Grant, mcavoy, & Keenan, 1982;Roper, 1977), five found no significant difference (anderson et al, 1972;Gaynor, 1981;Gilman, 1969;morrison, Ross, Gopalakrishnan, & Casey, 1995;Pysh, Blank, & lambert, 1969), and one found no feedback to be superior to KCR (Pridemore & Klein, 1995). The other, moore and smith (1964), found that KCR via teaching machine produced better within-program performance than KR and no feedback with construction-response materials, but not with multiple-choice materials.…”
Section: Knowledge Of Correct Responsementioning
confidence: 99%
“…moore and smith (1964) found that KR plus 1¢ per correct response produced better within-session performance than KR, KCR via teaching machine, and no feedback with multiple-choice materials, but not with construction-response materials. Pysh et al (1969) found no advantage of KCR with a self-tallied point per correct response over KCR or no feedback, but it was not clear what, if any, value the points had. Thorkildsen and Reid (1989) found no difference between conditions in which 2nd to 4th-grade students were presented with "correct" and either a graphic (e.g., smiley face) or a video segment following correct responding and a condition in which they only received "correct," when incorrect responses were followed by a short buzz in all conditions.…”
Section: Extra-instructional Consequencesmentioning
confidence: 99%